Alinhamento das estratégias de qualidade em função das exigências dos clientes: um estudo de caso em dois complexos automotivos - Viana, Ana Paula Severo (Universidade do Vale do Rio dos Sinos, 2014)
The suppliers to automakers, who work in the automotive complex format, typically called sistemist, focus their efforts on a supply of quality and meets all the requirements of its sole client. However, the same company that supplies two or more different automotive complex, ie two or more different brands of cars, struggling to align its service Quality Management System considering requirements of different customers. Considering the academic focus there are several studies addressing quality dimensions on the automotive industry. However, most of these studies have been focusing on the suppliers development and supply chain management without considering the supplier perspective and the advantages to integrate the requirements of its customers. To fill this gap, this study aims to propose a set of guidelines that meets the requirements of customers of a company that acts as sistemist in several units. Proposed guideline was based on the findings of a case study in two automotive, automotive complex located in the South and Southeast of Brazil. It begins by reviewing literature on Quality in Automotive Branch, Practices and Quality, Dimensions of Quality, Quality Management and Continuous Improvement Programs. Following, two articles present the evolution of quality - TQM (Total Quality Management) until the inclusion of contingency theory in quality management nowadays and a case study that analyzed the quality care in this supplier in its various units. As a result, it can be said that the greater the customer requirements exigency, the need for greater personalization of care for Quality. As suggested guidelines highlight the management of quality data, partnership with suppliers, focus on meeting customer requirements, involvement of senior leadership and employees.
Keywords: Qualidade; Ramo automotivo; Dimensões; Diretrizes; Sistemas de gestão; Cliente; Quality; Automotive industry; Dimensions; Guidelines; Management systems; Client; ACCNPQ::Engenharias::Engenharia de Produção